Les écarts de revenus dans les espaces transfrontaliers. Des moteurs de la mobilité transfrontalière - Belkacem, Rachid (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „This article analyses wage disparity in cross-border spaces in the Greater Region (GR) and Upper Rhine. It is based on the results of two studies, the first funded by EURopean Employment Services-Greater Region (EURES-GR) in 2022 and the other, ongoing, funded by EURopean Employment Services-T Upper Rhine. The analysis shows that this disparity can be explained by various economic, sociological and institutional factors, which operate on various levels: micro (relating to corporate policies), macro (relating to national taxation and social security policy) and meso (relating to economic sectors and branches). It begins by showing that salaries and their various component parts are hard to define, making cross-border comparison difficult. It then signals that while wages in Switzerland and Luxembourg are very attractive, they must be balanced against the cost of living and working hours, which differ on each side of the border. The main takeaway from this analysis is that the gap between wages and the cost of living is a significant driver of cross-border working in border regions.“
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lohnniveau; Mobilität; Schweiz; Wohnen; Wohnungsmarkt

Introduction. Cross-Border Inequalities. An Exploration in the Greater Region - Connor, Ulla; Aubry, Lola (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Mobilität; Wohnen; Wohnungsmarkt

Border-Crossing and “Temporal Otherness” in the Greater Region SaarLorLux. Residential Migrants’ Experiences of Divergence - Boesen, Elisabeth (Borders in Globalization Review, 2024)
Abstract: „This article deals with border-crossing and the experiences of “temporal otherness” of residential migrants who move their home from Luxembourg to the German side of the River Moselle. Research on temporal borders is highly influenced by a particular spatio-political relation: the West creating its underdeveloped other and coping with this other by controlling border-crossing, which in turn results in maintaining the idea of the other’s temporal remoteness. The Luxembourgish–German border region offers a complement to this perspective; here, one encounters migrants who move in the opposite temporal direction and appreciate certain forms of “being behind” in their new place of residence. These migrants must cope with divergences, i.e., with the fact that economic and socio-cultural conditions within their new socio-spatial universe, the cross-border region, have evolved differently. This article argues that the analysis of migrants’ memories is illuminating with respect to the question of the moral legitimacy of moving, and thus regarding the conception and everyday construction of cross-border communities. It sheds light on the fact that borderland research—by focusing on national differences and related conceptions of cross-border mobility and exchange—tends to ignore borderlanders’ notions of (regional) unity and related claims for convergence.“
Keywords: Fremdheit; Grenzarbeitnehmer; Mobilität; Sozialraum

„Die schlechten Straßen unter seinen Füßen“. Die Entwicklung der Mobilität der deutschsprachigen Belgier zwischen 1973 und 2023 - Sproten, Vitus (Föderalisierung, Strukturwandel, Erwartungshorizonte (1973–heute), 2023)
Keywords: Mobilität; Verkehr

Impacts de la mobilité résidentielle transfrontalière sur les espaces de la vie quotidienne des actifs du Luxembourg - Gerber, Philippe; Carpentier-Postel, Samuel (Economie et Statistique, 2012)
Abstract: „À partir d'une enquête effectuée par le CEPS/INSTEAD et la fondation Forum Europa, cet article analyse le phénomène de mobilité résidentielle transfrontalière et son impact sur les déplacements quotidiens. Réalisée au printemps 2008, cette enquête porte sur les actifs occupés résidant initialement au Luxembourg qui se sont installés dans un pays frontalier entre 2001 et 2007, tout en conservant leur emploi au Grand-Duché. Pour un grand nombre d'entre eux, le déménagement transfrontalier a permis d'accéder à un logement plus grand, voire d'en devenir propriétaire. Néanmoins, l'analyse des déplacements quotidiens montre que la grande majorité de ces personnes a dû consentir à de nombreuses concessions en termes de mobilité pour accéder au logement souhaité. Cela se ressent particulièrement pour le trajet domicile/travail dont la distance moyenne a doublé, ce qui a renforcé la dépendance des personnes concernées vis-à-vis de l'automobile. En dehors même du travail, la localisation des autres activités quotidiennes se trouve modifiée à la suite du déménagement. Des indicateurs synthétiques issus de la géostatistique permettent d'analyser la reconfiguration des lieux de ces activités. Malgré la relocalisation de beaucoup d'entre elles autour du nouveau lieu de résidence, une certaine inertie des comportements se traduit par le maintien de près d'une activité sur trois au Luxembourg. Dès lors, la dispersion des espaces d'activités augmente pour certains enquêtés. Cette dispersion, liée à la part des activités transférées vers le pays de résidence, varie fortement selon la nationalité; elle est plus forte pour les Luxembourgeois et pour les Portugais. Les personnes originaires des régions frontalières, qui retournent dans leur pays d'origine, gardent également près d'un quart de leurs activités au Grand-Duché: cela témoigne à la fois de l'importance du lieu de travail dans la structuration des espaces de vie quotidienne et d'un capital spatial déjà mis en évidence dans le cas d'actifs résidant au Luxembourg.“
Keywords: Grenzarbeitnehmer; Mobilität; Sozialraum; Wohnungsmarkt

Zum Modell des transnationalen sozialen Raums im Kontext von Grenzregionen. Theoretisch-konzeptionelle Überlegungen am Beispiel des Grenzgängerwesens - Wille, Christian (Europa Regional, 2009)
Abstract: „Angesichts fortschreitender Globalisierung gewinnen übernationale Sozialbeziehungen zunehmend an Bedeutung. Sie rücken als Forschungsgegenstände immer stärker in die Human- und Sozialwissenschaften ein und stellen die teilweise noch an ‚verankerten’ Lebensbedingungen orientierten analytischen Konzepte in Frage. So ist teilweise ein Wandel weg von statischen, homogenisierenden und abgeschlossenen Modellen von Gesellschaft, Kultur und Raum hin zu entsprechend offenen und dynamischen Konzepten auszumachen. Diese können wichtige Impulse geben für Fragestellungen und ihre theoretischen Annäherungen auf der kleinräumigen Ebene von benachbarten Grenzregionen. Im vorliegenden Beitrag soll hierfür das Modell des transnationalen sozialen Raums aufgegriffen und im Hinblick auf grenzüberschreitende Sozialverflechtungen zwischen europäischen Grenzregionen theoretisch-konzeptionell diskutiert werden. Dafür werden zunächst die Mobilitätstypen des Transmigranten und des Grenzgängers erläutert und auf empirischer Ebene beispielhaft Bezüge zu einer bei Grenzgängern in der „Großregion SaarLorLux“ durchgeführten Studie hergestellt. Das im Umfeld der Migrationsforschung entwickelte und vorzustellende Modell fokussiert auf dauerhafte Sozialzusammenhänge, die über Nationalstaaten hinausreichen und neue Vergesellschaftungszusammenhänge konstituieren, gleichwohl bleibt es in seiner Konzeption und Analytik weitgehend einem statischen und nationalstaatlichen Denken verhaftet. Vor diesem Hintergrund wird versucht, die zentralen Desiderata und mögliche Entwicklungsperspektiven für die Erforschung transnationaler Sozialzusammenhänge in Grenzregionen herauszuarbeiten. Given the continuing processes of globalisation, social networks that can be categorised as being above the national level are coming to the fore. They are also making constant headway as research topics in the human and social sciences by calling analytical concepts into question that are still geared towards “rooted” life conditions. For instance, there is a move away from statistical, homogenising and closed models of society, culture and space to more open and dynamic concepts that can provide important motivation for questions and their way they theoretically approach these issues on the small-space level of neighbouring border regions. This article will address the model of a transnational social space and discuss it in the framework of cross-border social interconnections between European border regions. It will start off by explaining the types of mobility that transmigrants and cross-border commuters have and then empirically and exemplarily linking this to a study made on cross-border commuters in the large-scale SaarLorLux region. The model to be presented here has been developed in the context of migration research and it focuses on permanent social connections that go beyond national states and constitute new connections of socialisation, even though its conception and analytical methods mostly remain dedicated to static thinking and to the national state. Given these facts, this article attempts to outline the central desiderata and potential development vistas for the research on transnational social relationships in border regions.“
Keywords: Arbeitnehmer; Arbeitsmigration; Grenzarbeitnehmer; Mobilität; Pendler; Sozialraum; Transnationalisierung